2018
DOI: 10.3389/fnins.2018.00062
|View full text |Cite
|
Sign up to set email alerts
|

Decoding English Alphabet Letters Using EEG Phase Information

Abstract: Increasing evidence indicates that the phase pattern and power of the low frequency oscillations of brain electroencephalograms (EEG) contain significant information during the human cognition of sensory signals such as auditory and visual stimuli. Here, we investigate whether and how the letters of the alphabet can be directly decoded from EEG phase and power data. In addition, we investigate how different band oscillations contribute to the classification and determine the critical time periods. An English l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…In particular, phase yielded strongly significant (p<0.001) decoding results in 9/10 subjects for the hard discrimination, while power did so only in 4/10 subjects. Primacy of phase information over power information, especially for distinguishing between activity patterns corresponding to different sensory stimuli, is in accordance with several prior reports in auditory, visual and tactile modalities (Luo and Poeppel, 2007;Howard and Poeppel, 2010;Ng et al, 2013;Gross et al, 2013;Schyns et al, 2011;Ronconi et al, 2017;Wang et al, 2018;Baumgarten et al, 2015), in motor signals (Hammer et al, 2013), as well as in more complex paradigms involving working memory and decision making (Rizzuto et al, 2003;Lopour et al, 2013). In our dataset and for the binary decoding analyses we considered, the combination of power and phase did not convey additional information beyond the one conveyed by the most informative between power and phase ( Fig.…”
Section: Stimulus Encoding Occurs Preferentially At Delta-theta and Gsupporting
confidence: 91%
“…In particular, phase yielded strongly significant (p<0.001) decoding results in 9/10 subjects for the hard discrimination, while power did so only in 4/10 subjects. Primacy of phase information over power information, especially for distinguishing between activity patterns corresponding to different sensory stimuli, is in accordance with several prior reports in auditory, visual and tactile modalities (Luo and Poeppel, 2007;Howard and Poeppel, 2010;Ng et al, 2013;Gross et al, 2013;Schyns et al, 2011;Ronconi et al, 2017;Wang et al, 2018;Baumgarten et al, 2015), in motor signals (Hammer et al, 2013), as well as in more complex paradigms involving working memory and decision making (Rizzuto et al, 2003;Lopour et al, 2013). In our dataset and for the binary decoding analyses we considered, the combination of power and phase did not convey additional information beyond the one conveyed by the most informative between power and phase ( Fig.…”
Section: Stimulus Encoding Occurs Preferentially At Delta-theta and Gsupporting
confidence: 91%
“…1-4 Hz). This finding was later investigated by another group using Hilbert transform, but found the information in the theta frequency band (4-8 Hz; Wang et al, 2018). Other studies found that signal power contained significant category-related information (Rupp et al, 2017;Majima et al, 2014;Miyakawa et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Later studies used Linear Discriminant Analysis (LDA) classifiers to discriminate up to four object categories utilizing the information content of those ERP components (Wang et al, 2012), which were later fused to improve previous decoding accuracies (Qin et al, 2016). However, these studies and others (Taghizadeh-Sarabi et al, 2015;Torabi et al, 2017;Wang et al, 2018) overlook the temporal dynamics of object encoding based on within-trial variations in the signals. To address this issue, researchers repeated the decoding procedure in short (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of speech decoding studies have been conducted using EEG recently such as for classification of imagined syllables (D'Zmura et al, 2009;Brigham and Vijaya Kumar, 2010;Deng et al, 2010), isolated phonemes (Chi and John, 2011;Leuthardt et al, 2011;Zhao and Rudzicz, 2015;Yoshimura et al, 2016), alphabets (Wang et al, 2018), or words (Porbadnigk et al, 2009;Nguyen et al, 2017;Rezazadeh Sereshkeh et al, 2017), the decoding performances have been intermediate, e.g., 63.45% for a binary (yes/no) classification (Rezazadeh Sereshkeh et al, 2017) or 35.68% for five vowel classification (Cooney et al, 2019a). There are inherent disadvantages in using EEG that may have contributed to the difficulty in attaining high decoding performance.…”
Section: Introductionmentioning
confidence: 99%